Current challenges in neurocysticercosis: Recent data and where we are heading - Coyle, Christina M. (2024)
Purpose of reviewNeurocysticercosis (NCC) is still a significant contributor to neurological disease in vast regions of the world, and increasingly diagnosed in nonendemic countries because of travel and immigration from endemic settings. There is a need for clinicians in endemic and nonendemic regions to understand the complexities of its diagnosis and management.Recent findingsRecent information on the performance and use of available imaging and immunodiagnostic tools as well as antiparasitic and anti-inflammatory therapeutic regimes were assessed.SummaryImaging and serology data should be assessed in the context of the specific type of NCC to improve diagnostic precision. In terms of therapeutic approaches, more controlled data is required on the efficacy and safety of combined antiparasitic therapy, and antiseizure and anti-inflammatory regimes should be optimized to minimize perilesional damage and reduce the risk of epilepsy.